Occupational Exposure to Particulate Matter and Volatile Organic Compounds in Two Indoor Cannabis Production Facilities. - Silvey, Brynne; Seto, Edmund; Gipe, Alexander; Ghodsian, Niloufar; Simpson, Christopher D (Annals of Work Exposures & Health, 2020)
Legal commercial cultivation and processing of cannabis is a rapidly growing industry in multiple countries. However, to date little effort has been made to characterize and identify the various occupational hazards that workers may be facing in the cannabis production industry, including airborne contaminants that may affect the human respiratory system. In the current study, we quantified occupational exposures to particulate matter (PM) and volatile organic compounds (VOCs) in various task zones of two indoor cannabis facilities in Washington State. Full-shift (8-h) area measurements of PM and VOCs were collected in each task zone. Measurement devices were placed near the employee's work area in order to attempt to estimate the personal exposure to the contaminants. In each task zone we measured particle number concentration, particle mass concentration (PMC), cumulative size distribution of the particles, and total terpene mass concentrations. The mean PMCs were greater in task zones that required the employees to manipulate the cannabis plants and materials. The arithmetic mean PMC for the trim task was 60 µg m−3, preroll task was 45 µg m−3, grow task was 42 µg m−3, and the referent office area was 27 µg m−3. When comparing each task zone PMC to the office referent PMC, the trim task, and the preroll task were significantly higher than the referent group (P -values both <0.05). The arithmetic mean terpene mass concentration for the trim task was 36 mg m−3, preroll task was 9.9 mg m−3, grow task was 15 mg m−3, and for the office referent space was 4.9 mg m−3. Compared with the office space, only the trim task area had significantly elevated terpene mass concentrations (P -value <0.01). We observed a weak but statistically significant correlation between PMC and total terpene mass concentrations (rho = 0.42, P < 0.02). Overall, we observed that exposures to respiratory hazards were highest in task zones where cannabis plants and material were manipulated by workers, including the trim, preroll, and the grow task areas. These observations can help inform the employer of the task zones where exposure to respiratory hazards are the highest, and where it may be beneficial to deploy control measures to reduce worker exposures.